METODOLOGINĖ DRAUGYSTĖ – TEORETIKŲ DIALOGAS - Tuleikytė, Julija (Problemos, 2014)
Zygmunt Bauman and Leonidas Donskis. Moral Blindness: Loss of Sensitivity in Liquid Modernity. Polity, 2013. 224 p. ISBN-10: 0745662757 Methodological Friendship – Dialog of Theoreticians Julija Tuleikytė >